(untitled) (Research, Society and Development, 2021)
In 1957, the economic development model was created for the state of Amazonas called Manaus Free Trade Zone (ZFM) through 3.173/57, which was later repealed by Decree-Law 288/63. As, constitutionally, the ZFM cannot be moved elsewhere, but nothing prevents the deposition of a similar model in other regions of the country or changes the taxes that are granted to the model the general objective of the research is to propose alternatives to the obstacles faced by the ZFM model that is failing to strengthen itself in the face of bureaucracy of the federal and state government. For the development of the research it was necessary to conduct a bibliographic study for the theoretical basis of the ZFM, tax incentives, Basic Productive Process (PPB) and Research, Development and Innovation (PD&I), in addition to field research to have a technical and specialized support to elaborate the proposals to the obstacles faced by the ZFM model. At the end of the research it is concluded that the objectives were achieved because alternatives were proposed for the better application of the model, among the suggestions of the study there are: to ensure that infraconstitutional norms are not emitted, that is, to guarantee the ZFM its existence with competitive and comparative advantages until the year 2073; review all regulatory frameworks for area concession, project approval and industrial monitoring; to show the ministries of the economy the economic dynamics produced in the ZFM creates financial impedance, among others.